The destruction of the nations and the promise of return: hermeneutical observations on the book of Deuteronomy - Braulik, Georg (Verbum et ecclesia, 2004)
Many Israelis, but also many Christian Palestinians, today understand the current conflict around the possession of the land in a Bible-oriented way. They associate it with the radical destruction of all inhabitants of the land and its subsequent occupation as it is formulated in Deuteronomy, namely as an instruction of God, and as portrayed in the book of Joshua, namely as an historical event. This typologising form of common hermeneutics contradicts both modern historiography on ancient Israel and the historic-critical exegesis of the two books as well as their interpretation in Jewish tradition. The campaign of the twelve-tribe nation under Joshua and the destruction of the peoples of Canaan is a theological, fictitious image of radical trust in God, which was designed under King Josiah for mythical ancient times. Neither the laws on warfare nor the promises of return in a synchronically read Deuteronomy know about any future violent conquest of the land of Canaan. The article analyses Israel's relation to the inhabitants of the land, especially in chapters 29-30, which are decisive for Moses’ vision of the future. Based on this analysis, it develops the hermeneutics of Deuteronomy for the directives on the destruction of the nations. Applying these directives typologically proves to be ruled out, both for the wars following the conquest of the land and for the return of Israel from exile.